(untitled) (Research, Society and Development, 2022)
Objective: To map existing literature on motoric cognitive risk syndrome and its associations with physical and psychological variables in community-dwelling older adults. Methodology: The indexed literature published in English, Portuguese and Spanish will be systematically searched on 8 databases (PUBMED, PUBMED PMC, EMBASE, BVS, COCHRANE, SCOPUS, WEB OF SCIENCE and AGELINE). Two authors will independently evaluate titles, abstracts and full-texts according to eligibility criteria. A customized data extraction form will be used to chart the data extracted from the studies. For consideration, studies must be in English, Portuguese or Spanish, involve studies with community-dwelling older adults (55 years old and over), men and/or women (mean age 60), gerontological literature that reports the syndrome in older adults, and observational, experimental and quantitative studies, besides reviews. Results: Results will be charted in a table and accompanied by a narrative summary.